2005
DOI: 10.21273/jashs.130.6.877
|View full text |Cite
|
Sign up to set email alerts
|

Transfer to Processing Tomato and Characterization of Late Blight Resistance Derived from Solanum pimpinellifolium L. L3708

Abstract: Late blight [caused by Phytophthora infestans (Mont.) de Bary] causes severe loss of tomato [Solanum lycopersicum L. (formerly Lycopersicon esculentum Mill.)] production in environments favorable to the pathogen. Researchers at the Asia Vegetable Research Development Center (AVRDC) identified resistance to late blight in an accession of S. pimpinellifolium [formerly L. pimpinellifoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 12 publications
1
18
0
2
Order By: Relevance
“…Phytophthora infestans is a biotrophic pathogen that is the causal agent of late blight (LB) in tomato. LB occurs worldwide and has long been prevalent in some countries, causing serious economic loss for field-grown tomatoes (Kim and Mutschler, 2005;Miranda et al, 2010); it is therefore regarded as a major threat to tomato production (Park et al, 2013). During the growing season of tomato, LB can occur at any time, which leads to brown-black, pathogen sporulation and water-soaked lesions on the foliage, stems and fruits of tomato (Fry et al, 1992;Park et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Phytophthora infestans is a biotrophic pathogen that is the causal agent of late blight (LB) in tomato. LB occurs worldwide and has long been prevalent in some countries, causing serious economic loss for field-grown tomatoes (Kim and Mutschler, 2005;Miranda et al, 2010); it is therefore regarded as a major threat to tomato production (Park et al, 2013). During the growing season of tomato, LB can occur at any time, which leads to brown-black, pathogen sporulation and water-soaked lesions on the foliage, stems and fruits of tomato (Fry et al, 1992;Park et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of L3708 was transferred into a series of processing tomato lines by the Cornell Univ. breeding program (Kim, 2003;Kim and Mutschler, 2005), using, as the initial starting material, two late blight-resistant BC 1 F 2 plants ('97A46' and '97A48', respectively) provided by R. Gardner. Lines '97A46' and '97A48' are BC 1 F 2 plants from the pedigree 'NC215E' x ('NC215E' x S. pimpinellifolium L 3708) selected as late blight resistant under natural infection (R. Gardner, personal communication).…”
Section: Tomato Lines Testedmentioning
confidence: 99%
“…of Agriculture (USDA) accessions NSL116890 and PI365957] as having strong resistance to late blight (AVRDC, 1994;Chunwongse et al, 2002). They generously provided L3708 to other breeding programs, which proceeded to transfer the resistance to tomato lines (AVRDC, 1999;Kim, 2003;Kim and Mutschler, 2005). When the resulting lines were grown together under natural infection, their degree of late blight resistance differed among the lines bred by different programs (R. Gardner, personal communication).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The work of Chen et al (2008) indicated that Ph-2 and Ph-3 complement each other and together offer resistance to a broader range of pathogen isolates compared to either gene alone. Evidence from Cornell University supported the presence of a second late blight resistance gene in L3708 Mutschler 2005, 2006) which interacted epistatically with Ph-3 (Kim and Mutschler 2005). Recently, Chen et al (2014) mapped qPh2.1 on chromosome 2 of L3708, which also contributed to late blight resistance.…”
mentioning
confidence: 98%